Stress Affects Central Compensation of Neural Responses to Cochlear Synaptopathy in a cGMP-Dependent Way - Savitska, Daria; Hess, Morgan; Calis, Dila; Marchetta, Philine; Harasztosi, Csaba; Fink, Stefan; Eckert, Philipp; Ruth, Peter; Rüttiger, Lukas; Knipper, Marlies; Singer, Wibke (Frontiers in Neuroscience, 2022)
In light of the increasing evidence supporting a link between hearing loss and dementia, it is critical to gain a better understanding of the nature of this relationship. We previously observed that following cochlear synaptopathy, the temporal auditory processing (e.g. auditory steady state responses, ASSRs) is sustained when reduced auditory input is centrally compensated. This central compensation process was linked to elevated hippocampal long-term potentiation (LTP). We further observed that, independently of age, central responsiveness to cochlear synaptopathy can differ, resulting in either a low or high capacity to compensate for the reduced auditory input. Lower central compensation resulted in poorer temporal auditory processing, reduced hippocampal LTP and decreased recruitment of activity-dependent brain-derived neurotrophic factor (BDNF) expression in hippocampal regions (low compensators). Higher central compensation capacity resulted in better temporal auditory processing, higher LTP responses, and increased activity-dependent BDNF expression in hippocampal regions. Here, we aimed to identify modifying factors that are potentially responsible for these different central responses. Strikingly, a poorer central compensation capacity was linked to lower corticosterone levels in comparison to those of high compensators. High compensators responded to repeated placebo injections with elevated blood corticosterone levels, reduced auditory brainstem response (ABR) wave I amplitude, reduced inner hair cell (IHC) ribbon number, diminished temporal processing, reduced LTP responses, and decreased activity-dependent hippocampal BDNF expression. In contrast, the same stress exposure through injection did not elevate blood corticosterone levels in low compensators, nor did it reduce IHC ribbons, ABR wave I amplitude, ASSR, LTP, or BDNF expression as seen in high compensators. Interestingly, in high compensators, the stress-induced responses, such as a decline in ABR wave I amplitude, ASSR, LTP, and BDNF could be restored through the ‘memory-enhancing’ drug phosphodiesterase 9A inhibitor (PDE9i). In contrast, the same treatment did not improve these aspects in low compensators. Thus, central compensation of age-dependent cochlear synaptopathy is a glucocorticoid and cyclic guanosine-monophosphate (cGMP)-dependent neuronal mechanism that fails upon a blunted stress response.